ANALISIS BEBAN KERJA FISIK DENGAN LINE BALANCING PADA PT. XYZ (PERUSAHAAN ALAT PEMBERSIH DAN PELENGKAPNYA) - Nathaniel, Nicholas Adrian; Widodo, Lamto; Andres (Universitas Tarumanagara, 2023)
Today's increasingly rapid industrial development means that companies must pay attention to several things during the production process so that they can face the tough competition, one of which is by paying more attention to the quality of their products and the risks that could result in the product becoming defective so that it can meet customer satisfaction. Labor is one of the important factors that a company has, for this reason, an even workload and in accordance with capacity is one of the things that greatly influences the performance of the workforce to produce products that comply with standards. This analysis uses several methods, including: cardio vascular load, full time equivalent, and line balancing. This research aims to provide suggestions for improvements that are expected to reduce the workload of production workers and waiting times at PT. From the research carried out, it can be concluded that materials mixing workstations experience excessive workload or are overloaded so that work on these workstations is less than optimal, so that more operator power is needed or additional operators are needed at materials mixing workstations. The packing work station experiences underload or underload so it is necessary to reduce operators so that it does not become a burden on the company, especially in salary expenses.